The abundance of canopy arthropods in South Sumatra (Indonesia) freshwater swamp main and ratooned rice applied with bioinsecticides and synthetic insecticide - GHANNI PRABAWATI; Siti Herlinda; YULIA PUJIASTUTI (Society for Indonesian Biodiversity, 2019)
Abstract. Prabawati G, Herlinda S, Pujiastuti Y. 2019. A comparative study on the arboreal arthropod abundance of rice fields between applied with fungal bioinsecticides and abamectin in the freshwater swamp of South Sumatra, Indonesia (Study case in the main and ratoon rice fields). Biodiversitas 20: 2921-2930. Ratoon rice has been cultivated by local farmers in South Sumatra and can be a source of habitat and niches for the main rice arthropods. The study aimed to compare the abundance of arthropods between main and rationed rice field applied with fungal bioinsecticides and abamectin. This study used bioinsecticides from fungi of Beauveria bassiana, Metarhizium anisopliae, and Cordyceps militaris and control using abamectin. Arboreal arthropods sampled using a sweep net. The abundance of arthropods in the main rice tends to be higher than in ratoon. Spiders found during the two rice seasons were Araneidae, Linyphiidae, Lycosidae, Oxyopidae, Salticidae, Theridiidae, Tetragnathidae, Theridiosomatidae, while predatory insects found were Mantidae, Coenagrionidae, Staphylinidae, Anthicidae, Latridiidae, Formicidae, Coccinellidae, Coccinellidae, Tettigoniidae, Miridae, Carabidae. The fungal bioinsecticides did not reduce the predatory arthropod abundance but the abamectin caused a decrease in the abundance of all guilds. The most drastic decrease was found in web-building spiders. The movement of hunting spiders and the predatory insects of the main to ratoon rice was faster than that of web-building spiders. The existence of ratoon rice could become habitats and niches for arthropods from the main rice. For this reason, controlling the herbivore insects could use bioinsecticides derived from entomopathogenic fungi.